FAKTOR - FAKTOR PENYEBAB TERJADINA PENGGANGGURAN (STUDI KASUS KABUPATEN ACEH UTARA) - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2017)
This study aims to determine the factors that cause the occurrence of unemployment in North Aceh . Data used in this research is quantitative secondary data are annual data in the form of numbers . Source of data obtained from the Central Statistics Agency report ( BPS ) North Aceh District from 2003 until 2013. From the results obtained regression coefficient R = 0.032074 which shows the relationship variable partial unemployment on the unemployment rate . The regression results obtained value of R2 = 0.225659 , which means that the variable labor force and population affect the unemployment rate ( dependent variable ) in North Aceh . Partially t-test of the labor force amounted to 1.069654 . T-test value (1.069654) < t - table ( 2.22814 ) , meaning HI1 H01 is rejected and accepted , which means the labor force do not have a significant effect on the unemployment rate in northern Aceh . t - count population of 1.468538 . T-test value (1.468538) < t - table ( 2.22814 ) , meaning HI2 H02 is rejected and accepted , which means the number of people do not have a significant effect on the unemployment rate in northern Aceh .